(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The current research seeks to determine the impact of the multiple life cycle in enhancing the sustainability of industrial products within the field side represented by the Babylon battery factory affiliated to the General Company for the Automotive and Equipment Industry, To achieve the goal of the research, a hypothetical research model was built in light of the formulation of the research hypotheses represented in the first hypothesis: there is no significant statistically significant correlation between the multiple life cycle strategies (combined and individually) and the sustainability of the product in the factory under study, The second hypothesis: there is no effect without statistical significance for multiple life cycle strategies (combined and individually) in product sustainability in the factory under search. A set of conclusions has been reached, the most important of which is that there is a significant correlation and a varying level of impact for each of the various life cycle strategies on the sustainability of the product combined within the field aspect under consideration. Depending on the conclusions reached by the research, a number of recommendations were presented that are consistent with these conclusions, the most important of which is supposed to the management of the factory under search to pay greater attention to the entrance of the multiple life cycle and that for the provisions of closing the cycle of material flow, as well as to make full use of the application of this entrance In the factory under search.